Teacher Support and Career Decision-Making Self-Efficacy Across Gender - Arif Sahin; Dwi Yuwono Puji Sugiharto; Sunawan; Mulawarman (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
The career decision-making process is a critical developmental task during adolescence, especially for senior high school students transitioning from further education to employment. This study examined the effect of teacher support on career decision-making self-efficacy (CDMSE), with gender tested as a potential moderator, among 542 students from public senior high schools in Semarang City, Indonesia. Data were analyzed using Hayes’ PROCESS Model 1. The findings revealed that teacher support significantly predicted students’ CDMSE (β = 0.60, p < .01, 95% CI: 0.50–0.72). Gender differences were also observed, with female students reporting higher CDMSE than male students (β = -2.40, p < .05, 95% CI: -4.46 to– 0.35). However, the interaction between teacher support and gender was non-significant (β = -0.19, p > .05), indicating that teacher support contributes similarly to CDMSE across genders. This study offers novel empirical evidence from the Indonesian secondary school context, enriching the Social Cognitive Career Theory (SCCT) through gender-based moderation testing. Practically, the findings highlight the importance of strengthening teachers’ roles in school-based career guidance to enhance students’ confidence in making informed career choices. Keywords: career decision-making self-efficacy, gender, teacher support